Cover Picture: Highly Selective Reduction of α, β‐Unsaturated Aldehydes and Ketones under Ambient Conditions using Tetraalkylphosphonium‐based Ionic Liquids (42/2018). Issue 42 (9th November 2018) - Ralphs, Kathryn; McCourt, Éadaoin; Ormandy, Christopher; Carneiro de Souza, Thiago A.; Nockemann, Peter; Jacquemin, Johan; Manyar, Haresh G.
Abstract : The cover picture shows highly selective reduction of cinnamaldehyde to cinnamyl alcohol facilitated in ionic liquids. In this work, a new protocol for selective reduction of α, β ‐unsaturated aldehydes and ketones, has been developed in presence of ionic liquids by using NaBH4 as reducing agent. Under optimised conditions in [P6, 6, 6, 14 ][N(CN)2 ] ionic liquid, 97% conversion of cinamaldehyde with 100% selectivity to cinnamyl alcohol was achieved with enhanced reaction rates. The reaction protocol is facile and [P6, 6, 6, 14 ][N(CN)2 ] ionic liquid was easily recycled without any noticeable loss of activity and selectivity. More information can be found in the Full Paper by Manyar et al . (DOI: 10.1002/slct.201801092 ).